Modeling a process of formation of innovative orientation of professional-pedagogical competence of students of engineering and pedagogical higher education institutions - Nizhnik О. (Problems of Engineer-Pedagogical Education, 2020)
The essence and content of innovative activity in general and in higher education institutions in particular are analyzed. It is determined that pedagogical innovation can be considered as the end result of innovation, which is embodied in the form of a new content, method, form of organization of the educational process or an improved learning tool that is used in practical activities, or in a new approach to educational services. The classification of pedagogical innovations is offered; in particular innovations are classified by types of activity; by the nature of the changes made; by the scale of the changes; by the scale of use; by the source of their origin, etc. It is proved that the main goal of introducing innovations in the educational space of higher education institutions is to improve the quality of formal training of specialists. One of the means to achieve it in modern conditions is to "instill" an innovative culture in students. The above suggests the need for introducing an innovative approach into the basis of the process of formation of professional and pedagogical competence, which is ensured by the implementation in the process of formal training of students of engineering and pedagogical higher education institutions of a number of principles, in particular innovative orientation of educational progress, interdisciplinary integration, target unity, general professional orientation, unity of theory and practice, continuity, intensification and optimization of education, personal students’ advances, advanced studies, etc. It is determined that the process of forming innovative culture of an individual in the system of engineering and pedagogical higher education institutions should be considered in the unity of the innovative culture of the teacher, student and educational process management subjects. And the innovative orientation of professional and pedagogical competence of a specialist is achieved as a result of complex changes in all the components of the holistic structure of the educational process, which together ensure the individual’s readiness and aptitude for innovative activities.